Climate Change and Carbon Sequestration - Srinivasarao, Ch.; Kundu, Sumanta; Thakur, Pravin B. (International Journal of Economic Plants, 2015)
Industrial revolution has led footprints towards changes in atmospheric composition since its initiation. The Earth’s average surface temperature increased by 0.74 oC in the late 19th century, and is projected to increase by >1.5 oC (IPCC Fifth Assessment Report). In the scenarios of higher rates of emissions, temperature is likely to exceed 2oC and could be as much as 4 oC at the end of 21st century. Climatic vulnerability includes increased frequency of extreme events such as cyclones, floods, cold-hot waves and droughts. Temperature increase is associated with a rise in greenhouse gases, deforestation, agriculture and industrial processes. CO2, methane (CH4) and nitrous oxide (N2O) are the prime GHGs which are associated with agriculture. Indian agriculture, on which about 60% of the populations are dependent for livelihood may have impacted directly or indirectly by abrupt climate change. On the other hand Soil organic matter (SOM) in soils is a strong determinant of soil quality and controls the physico-chemical and biological soil processes. A warming climate and decreasing soil moisture limits the soil functions. One of the important climate smart agricultural practices is reduction of CO2 emission by restoring soil organic carbon (SOC) pool and improving soil quality which can address both the problems of food security and climate change.